The Role of Self-Empowerment, Interest, and the Role of Husbands of Women's Motivation and Decision-Making as Entrepreneurs: A Conceptual Framework and Empirical Evaluation - Elsa Rahima; Rahmad Solling Hamid; Sofyan Syamsuddin; Muhammad Ikbal (UM Purwokerto Press, 2024)
Background: In the realm of entrepreneurship, women's engagement has gained prominence, necessitating an exploration of the multifaceted factors that underpin their motivation and decision-making processes. This study seeks to develop a comprehensive conceptual framework and conduct empirical assessments to elucidate the contributions of self-empowerment, interests, and the role of husbands in shaping women's entrepreneurial motivation and decision-making dynamics. This study aims to examine the relationship between self-empowerment, interest, the role of husbands, motivation, and decision-making as women entrepreneurs. Method: The empirical analysis was conducted using a sample of 150 women entrepreneurs. This study used an online survey for data collection. After passing reliability and validity tests, the data were analyzed with partial least squares structural equation modeling. Results: The research results indicate that self-empowerment has a significant positive direct influence on motivation. Interest also has a significant direct positive influence on motivation. Furthermore, the role of husbands has no significant effect on motivation. Finally, motivation also has a significant positive influence on decision-making as an entrepreneur. Conclusion: This study has established a robust conceptual framework and conducted empirical evaluations that shed light on the intricate interplay of self-empowerment, interests, and the role of husbands in influencing women's motivation and decision-making as entrepreneurs. These findings provide valuable insights for policymakers, practitioners, and researchers, emphasizing the importance of tailored strategies to support and empower women in the entrepreneurial domain, ultimately fostering their success and contribution to economic growth.